Socio-Economic Inequity and Decision-Making under Uncertainty: West African Migrants’ Journey across the Mediterranean to Europe - Dinbabo, Mulugeta F. (2021)
Understanding the nexus between poverty, inequality and decision-making under uncertainty in migrants’ journeys across the Mediterranean Sea to Europe remains a significant challenge, raising intense scholarly debate. Several suggestions have been offered on how to reduce migrants’ journeys across the Mediterranean Sea to Europe in several guises, including the formulation and implementation of proper social, political and economic policies in Africa. Despite all odds and challenges, migrants from Africa cross state boundaries and stay in transit state(s) for limited periods, en route the Mediterranean Sea to Europe. Underpinned by different migration theories and conceptual frameworks, our study applied a qualitative methodology to examine why migrants decide, under uncertainty, to cross the Mediterranean Sea from their countries of origin to the ultimate destinations in Europe. While focusing on the life experiences of purposively selected migrants from West Africa, the research seeks to address the underlying factors of irregular migration. The result of this empirical study clearly illustrates that limited access to opportunities, poverty and unemployment amidst precarious development challenges and the youth population bulge, exacerbate Africa’s migration crisis. The study finally brings into focus empirical observations and provides suggestions for stakeholders’ engagement in addressing African migration challenges.